A 1, 3, 2‐Diazaphospholene‐Catalyzed Reductive Claisen Rearrangement. Issue 26 (16th May 2019) - Reed, John H.; Donets, Pavel A.; Miaskiewicz, Solène; Cramer, Nicolai
Abstract: 1, 3, 2‐Diazaphospholenes (DAPs) are an emerging class of organic hydrides. In this work, we exploited them as efficient catalysts for very mild reductive Claisen rearrangements. The method is tolerant towards a wide variety of functional groups and operates at ambient temperature. Besides being enantiospecific for substrates with existing stereogenic centers, the diastereoselectivity can be switched by varying solvents and DAP catalysts. The reaction kinetics show direct rearrangements of O‐bound phospholene enolates and provide a proof‐of‐principle for catalytic enantioselective reactions. Abstract : A DAP hand at rearrangement : 1, 3, 2‐Diazaphospholenes (DAPs) are efficient catalysts for ambient‐temperature reductive Claisen rearrangements. This method tolerates a wide variety of functional groups and is enantiospecific for substrates with existing stereogenic centers. The diastereoselectivity can be controlled by the choice of solvent and DAP catalyst.